Diploid – triploid and tetraploid mosaicism in a child with cryptogenic cirrhosis and membranous glomerulonephritis: a causal relationship or coincidental association? - Topaloğlu, Rezan; Aktaş, Dilek; Bakkaloğlu, Ayşın; Balcı, Sevim; Doğru, Deniz; Öztürk, Ramazan (The Turkish Journal of Pediatrics, 1998)
We present a seven-year-old boy with cryptogenic cirrhosis, membranous glomerulonephritis, mild mental retardation and mild dysmorphic changes. Chromosomal analysis showed diploid, triploid and tetraploid mosaicism which was detected both by cytogenetic study and flow cytometric analysis of nuclear DNA content. Complete tetraploidy and triploidy, usually lethal, are rare chromosomal disorders. This is the first reported case of diploid-triploid-tetraploid mosaicism with cryptogenic cirrhosis and membranous glomerulonephritis.